PENGARUH WEBSITE DESIGN QUALITY, SERVICE QUALITY, TRUST DAN SATISFACTION TERHADAP REPURCHASE INTENTION (STUDI KASUS: TOKOPEDIA.COM) - Innocentius Bernarto; Nicholas Wilson; Ian Nurpatria Suryawan (Jurnal Manajemen Indonesia, 2019)
The purpose of this study is to analyze and test: 1. Whether Website Design Quality from Tokopedia.com has a positive effect on Trust, 2. Does Website Design Quality from Tokopedia.com have a positive effect on Satisfaction, 3. What is Service Quality from Tokopedia .com has a positive effect on Trust, 4. Whether Service Quality of Tokopedia.com has positive effect on Customer Satisfaction, 5. Does Satisfaction have positive effect on Trust, 6. Does Customer Satisfaction have positive effect on Repurchase Intention, 7. Whether Trust have a positive effect on Repurchase Intention. Survey methods are used in this study. Data collection was done by using questionnaire instrument. The target population of research is all of the UPH students. The sample size was determined for 93 samples. The sampling technique is done with convenience sampling. Partial least Square-Structural Equation Modeling approach with SmartPls program is used for data analysis. The results show that web design quality has no positive effect on trust. Similarly, satisfaction has no positive effect on repurchase intention. Then, web design quality and service quality have a positive effect on satisfaction. Service quality and satisfaction have a positive effect on trust. Finally, trust has a positive effect on repurchase intention. Keywords—Website Design Quality, Service Quality, Trust, Kepuasan, Repurchase Intention. Abstrak Tujuan dari penelitian ini adalah untuk menganalisis dan menguji: 1. apakah Website Design Quality dari Tokopedia.com berpengaruh positif terhadap Trust, 2. apakah Website Design Quality dari Tokopedia.com berpengaruh positif terhadap Satisfaction, 3. apakah Service Quality dari Tokopedia.com berpengaruh positif terhadap Trust, 4. apakah Service Quality dari Tokopedia.com berpengaruh positif terhadap Satisfaction Pelanggan, 5. apakah Satisfaction berpengaruh positif terhadap Trust, 6. apakah Satisfaction pelanggan berpengaruh positif terhadap Repurchase Intention, 7. apakah Trust berpengaruh positif terhadap Repurchase Intention. Metode survei digunakan di dalam penelitian ini. Pengumpulan data dilakukan dengan menggunakan instrumen kuesioner. Target populasi penelitian adalah seluruh mahasiswa UPH. Jumlah sampel ditentukan sebesar 93 sample. Teknik pengambilan sampel dilakukan dengan convenience sampling. Pendekatan Partial least Square-Structural Equation Modeling dengan program SmartPls digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa web design quality tidak berpengaruh positif terhadap trust. Begitu juga, satisfaction tidak berpengaruh positif terhadap repurchase intention. Kemudian, web design quality dan service quality berpengaruh positif terhadap satisfaction. Service quality dan satisfaction berpengaruh positif terhadap trust. Terakhir, trust berpengaruh positif terhadap repurchase intention. Kata kunci—Website Design Quality, Service Quality, Trust, Kepuasan, Repurchase Intention